An observational study to evaluate fall in hemoglobin following abortions conducted by misoprostol and surgical methods - Das, Subrata; Wilson, Swapnil; Xess, Somila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Over the past three decades, medical methods of abortion have been developed throughout the world and are now the standard methods of providing abortion care in addition to surgical methods. There are various differences between the two methods. In this study, evaluating the fall in haemoglobin levels in abortions conducted by misoprostol and D and E in women with pregnancy failure. Methods: Total of 80 women who fulfilled the criteria were included in the study. Inclusion and exclusion criteria applied and Hb levels noted on day 1 and 15 during follow up. In addition to this induction abortion interval and side effects of both the methods were also studied. Participants assigned to medical treatment received 800 μg of misoprostol inserted into posterior vaginal fornix i.e., day 1st and repeat dose on day 3 if no expulsion. Follow up done after 1 week and 15 days, if there was no expulsion, suction and evacuation was done. Participants assigned to dilatation and evacuation group would undergo the procedure in operation theatre. Statistical analysis done. Results: The mean induction to abortion interval in the misoprostol group was 9.1±2.1 hours (mean±SD). The mean hemoglobin level in the misoprostol group on day 15 was 9.7±1.12 and that in the D and E group was 10.26±1.31 p value (0.04), statistically significant. Conclusions: Proper counseling of the side effects in both the methods and prompt action to alarming signs are required to avoid major disaster.